PENERAPAN STRATEGI DRA (DIRECTED READING ACTIVITY) UNTUK MENINGKATKAN KEMAMPUAN SISWA DALAM MEMBACA PEMAHAMAN - Dasri Dasri (JURNAL PENDIDIKAN ROKANIA, 2017)
The purpose of this study is to determine the ability to read students' understanding through the implementation of DRA (Directed Reading Activity) strategy in Indonesian Lessons.Subjects in this study were students of Class VI SDN 015 Rokan IV Koto Kab. Rokan Hulu of the academic year2016-2017 with a total of 20 students. While the object in this study is the application of DRA Strategy. The steps taken in classroom action research are: 1) Planning / preparation of action, 2) Implementation of action, 3) Observation, and 4) Reflection. The results of the discussion and analysis found thatthrough DRA Strategy (Directed Reading Activity) can improve the ability to read comprehension on the Indonesian Language Lesson students of Class VI SDN 015 Rokan IV Koto Rokan Hulu District. Based on the results of the study note that Reading Ability Understanding students in the first cycle increased 63.2, while in cycle II there was an increase with average classical 86 with high category.